The Effect of Organizational culture and Auditor competence on Auditor performance - Yanuar Tiar Megantara; Nur Zeina Maya Sari; Dian Widyantini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the influence of organizational culture and auditor competence on auditor performance at the Bandung City Regional Inspectorate. The data used are primary data in the form of questionnaires distributed to auditors at the Bandung City Regional Inspectorate. The method used in this study is descriptive and verification methods. The population in this study were auditors at the Bandung City Regional Inspectorate. A sample of 33 respondents was taken. The type of data used in this study is primary data. This study aims to determine the influence of organizational culture and auditor competence on auditor performance at the Bandung City Regional Inspectorate. This study was conducted using observation, interview, and questionnaire data collection techniques on employees of the Bandung City Regional Inspectorate processed using SEM-PLS. The results of this study are expected to be a solution to solve problems regarding employee performance at the Bandung City Inspectorate. The results of this study indicate that organizational culture and auditor competence have a positive and significant effect on auditor performance.